Classification of Alumni Employment Fields of the Nursing Study Program at Politeknik Nusa Utara Using K-Means Clustering Method - Noldy Sinsu; Arifin P Tindi; Oktavianus Lumasuge (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2025)
Tracer study is a trace trace of graduates performed every year after graduation competence in the world of work. In addition, tracer studies are also a prerequisite for obtaining accreditation from the National Council for Accreditation of Education. Alumni field classification can be done using the K-means Clustering method to group data based on data feature similarities. This research aims to facilitate the analysis of the classification of alumni's field of work. Job classification data was obtained from the alumni tracer on the Nursing Studies Program. The study analyzed a healthcare tracer that contains a curriculum cover from 2014 to 2022 using a K-means Clustering algorithm using Microsoft excel. The attributes used are domicile, admission time, graduation time, and workplace authority. The formed cluster is two clusters. The results of this research can be used as a basis for decision-making to determine the promotion strategy as well as the preparation of curricula based on the cluster formed by the Nursing Studies Program available at the Health Department of Politeknik Nusa Utara.